Diagnosis of malaria by the optimal method in children with routine microscopy and its comparison - Saheb, Shaik Ateal (International Journal of Contemporary Pediatrics, 2020)
Background: The term malaria (meaning bad air of the marsh and swampland) first originated in the 17th century. Malaria is one of the most serious medical conditions, Malaria causes symptoms which usually include fever, fatigue, vomiting, and headaches. It may cause yellow skin, seizures, coma, or death in extreme cases. The population of tribal areas of Andhra Pradesh, Tamilnadu, Karnataka, Chhattisgarh, Gujarat, Bihar, Orissa, Northeastern states are contributing 50% of cases of Plasmodium falciparum. Methods: All the clinically suspected cases of Malaria, ‘The optiMAL’ test was done at the bedside and simultaneously thick and thin smears are prepared and sent for microscopic examination. Study was carried out at Narayana Medical College, Nellore, Andhra Pradesh, India. The total number of patients in our study was 150. 1-14 years of age were included in the present study after applying the inclusion and exclusion criteria. Results: The ‘OptiMAL’test method had excellent sensitivity and specificity (100%) for detecting plasmodium vivax, very good sensitivity, and specificity (98.57%, 100%) for detecting plasmodium falciparum. The optimal test had a positive predictive value of 100%, the negative predictive value of 98.61% with p-value <0.001. Conclusions: Our study has shown that the ’OptiMAL’ test is an easy and successful diagnostic test that can be performed at the bedside for malaria diagnosis. This is very similar to traditional microscopy and do not need highly qualified workers to conduct experiments or interpret.